Industry Funding and Cholesterol Research: A Systematic Review. Issue 2 (March 2021) - Barnard, Neal D.; Long, M. Blaire; Ferguson, Jennifer M.; Flores, Rosendo; Kahleova, Hana
The effect of diet on blood cholesterol concentrations has become controversial. We assessed whether industry-funded studies were more likely than non–industry-funded studies to report conclusions that were not supported by their objective findings. PubMed and Cochrane Central Register of Controlled Trials searches through March 8, 2019, yielded 211 relevant articles. The percentage of industry-funded studies increased from 0% in the 1950s to 60% for 2010 tp 2019 ( P < .001). Of 94 non–industry-funded intervention studies for which the effect of egg ingestion on cholesterol concentrations could be determined, net cholesterol increases were reported in 88 (93%) studies (51% statistically significant, 21% not significant, 21% significance not reported). Among 59 industry-funded intervention studies, net cholesterol increases were reported in 51 (86%) studies (34% statistically significant, 39% not significant, and 14% significance not reported). No studies reported significant cholesterol decreases. Nonsignificant net cholesterol decreases were reported by 6 (6%) non–industry-funded and 8 (14%) industry-funded studies. However, 49% of industry-funded intervention studies reported conclusions that were discordant with study results (ie, net cholesterol increases were described as favorable in the articles' stated conclusions), compared with 13% of non–industry-funded studies. Readers, editors, and the public should remain alert to funding sources in interpreting study findings and conclusions.